Towards customer-induced service orchestration: requirements for the next step of customer orientation - Alt, Rainer; Ehmke, Jan Fabian; Haux, Reinhold; Henke, Tino; Mattfeld, Dirk C.; Oberweis, Andreas; Paech, Barbara; Winter, Alfred (Electronic markets, 2019)
This position paper acknowledges that customer orientation is a key requirement for companies to be competitive in the marketplace. Customer orientation has led to concepts, such as personalization, one-to-one-marketing, mass customization and co-creation, which all strive for a strong alignment of individual customer demands and encounters with a company’s offerings. Despite the customer is increasingly regarded as an active partner, the overall perspective of customer orientation is still mainly provider-oriented. Adopting the perspective of customers, as argued in this position paper, would help recognizing that customer problems are often broader and more complex than the solutions of single providers. While intermediaries and, more recently, assistants based on artificial intelligence, have emerged to address this demand, their approaches are typically little transparent and follow a black-box paradigm. Using examples from multiple application domains, this position paper proposes elements that need to be addressed to overcome these shortcomings. The concept of customer-induced service orchestration and management shall empower customers to combine services from multiple service providers in order to address their problems in a transparent and white-box way. This approach could represent an important next step in customer orientation.
Gesehen am 24.07.2019